Trichinella spiralis secretes abundant unencapsulated small RNAs with potential effects on host gene expression. Issue 9 (August 2020) - Taylor, Peter J.; Hagen, Jana; Faruqu, Farid N.; Al-Jamal, Khuloud T.; Quigley, Bonnie; Beeby, Morgan; Selkirk, Murray E.; Sarkies, Peter
Graphical abstract: Highlights: Trichinella spiralis adults and larvae secrete abundant small (18–40 nt) RNAs including microRNAs (miRNAs). Both adults and larvae secrete similar quantities of exosomes. Adult secreted miRNAs are contained within exosomes. Surprisingly, larvae, which live intracellularly within muscle cells secrete miRNAs which are not contained within exosomes. Direct release of unencapsulated miRNAs by intracellular larvae might be a way to influence host cell gene expression. Abstract: Many organisms, including parasitic nematodes, secrete small RNAs into the extracellular environment, largely encapsulated within small vesicles. Parasite-secreted material often contains microRNAs (miRNAs), raising the possibility that they might regulate host genes in target cells. Here we characterise secreted RNAs from the parasitic nematode Trichinella spiralis at two different life stages. We show that adult T. spiralis, which inhabit intestinal mucosa, secrete miRNAs within vesicles. Unexpectedly, T. spiralis muscle stage larvae, which live intracellularly within skeletal muscle cells, secrete miRNAs that appear not to be encapsulated. Notably, secreted miRNAs include a homologue of mammalian miRNA-31, which has an important role in muscle development. Our work therefore suggests that RNAs may be secreted without encapsulation in vesicles, with implications for the biology of T. spiralis infection.